2017
DOI: 10.1530/rep-16-0654
|View full text |Cite
|
Sign up to set email alerts
|

Bovine embryo-oviduct interaction in vitro reveals an early cross talk mediated by BMP signaling

Abstract: Signaling components of bone morphogenetic proteins (BMPs) are expressed in an anatomically and temporally regulated fashion in bovine oviduct. However, a local response of this signaling to the presence of the embryo has yet to be elucidated. The aim of the present study was to evaluate if early embryo-oviduct interaction induces changes in the gene expression of BMP signaling components. For this purpose, we used an co-culture system to investigate the local interaction between bovine oviductal epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…The hypothesis that the presence of an embryo is able to elicit changes in the oviduct epithelium transcriptome is based on findings from mammals such as mice (Lee et al, 2002), swine (Almiñana et al, 2012) and horses (Smits et al, 2016). Furthermore, in support of the hypothesis that the embryo is able to communicate with the oviduct, in vitro studies have shown that bovine oviduct epithelial cell (BOEC) transcriptome is affected by the embryo presence (García et al, 2017;Schmaltz-Panneau et al, 2014). In cattle, while the presence of multiple embryos in the oviduct resulted in the detection of differentially expressed genes (Maillo et al, 2015), attempts to detect the effect of a single bovine embryo on the oviductal isthmus were unsuccessful (Maillo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis that the presence of an embryo is able to elicit changes in the oviduct epithelium transcriptome is based on findings from mammals such as mice (Lee et al, 2002), swine (Almiñana et al, 2012) and horses (Smits et al, 2016). Furthermore, in support of the hypothesis that the embryo is able to communicate with the oviduct, in vitro studies have shown that bovine oviduct epithelial cell (BOEC) transcriptome is affected by the embryo presence (García et al, 2017;Schmaltz-Panneau et al, 2014). In cattle, while the presence of multiple embryos in the oviduct resulted in the detection of differentially expressed genes (Maillo et al, 2015), attempts to detect the effect of a single bovine embryo on the oviductal isthmus were unsuccessful (Maillo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the cycle threshold (CT) or the cycle during the log‐linear phase of the reaction at which fluorescence increased above background was determined for each sample. The ΔCT value was determined by subtracting the endogenous control ( ACTB; reference gene previously tested in oviduct epithelial cells in in vivo (Maillo et al, ) and in vitro (García et al, ) studies) C T value for each sample from each gene CT value of the sample. Calculation of ΔΔ C T involved using the highest sample Δ C T value (i.e., the sample with the lowest target expression) as a constant to subtract from all other Δ C T sample values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between the ipsi-and contralateral sides were observed. García et al (2017) used an in vitro model to correlate processes in bovine oviduct epithelial cells with the developmental stage of the embryos. For this, Fallopian epithelial cells were cultured in vitro and covered with a woven polyester mesh having a grid size of 41 × 41 openings.…”
Section: Exchange Of Signals Between Embryo and Oviduct In Cattlementioning
confidence: 99%
“…In several studies bovine embryos were cocultured with OEC to mimic the maternal environment in vitro. These experiments demonstrated bi-directional responses at the transcriptional level from both the maternal and embryo side (Schmaltz-Panneau et al, 2014;Garcia et al, 2017). However, OEC were subjected to multiple embryos and/or prolonged coincubation, which does not ideally imitate the in vivo situation in the monovulatory cow.…”
Section: Co-culture Of Embryos With Epithelia Of the Frtmentioning
confidence: 99%